Disparity in Economic Growth Between Regencies and Cities in the Province of Maluku - Yunita Ayu (Green Publisher Indonesia, 2024)
This research aims to analyze and know the structure of economic growth in each district and city in Maluku Province based on economic growth and Gross Regional Domestic Product per capita from 2018 to 2021 and to find out the inequality of economic growth in each regency/municipality area. The measurement tools used for analysis are the Klassen Typology approach and the Williamson Index. The Klassen Typology analysis study show that there are four regions in the developed and fast categories, namely those with a high rate of economic growth followed by a high rate of GDRP, then in the category of underdeveloped areas it is found that it exceeds half of the total area in Maluku Province in analysis that is equal to five areas. Williamson's index analysis shows that development income disparities between regions in Maluku Province are at a low level in most regions due to growth and income per capita is quite high, exceeding the average for Maluku Province.